Actions of thyroid hormone on myocardial contractility in the intact animal - Lubbe, Wilhelm Frederick (Department of Public Health and Family Medicine, 2020)
The central role of the mammalian heart in the circulation was recognised by Nei Chung when he wrote in his Third Book of the Yellow Emperor's Classic of Internal Medicine (2698 - 2598 B.C.): Treatise on the Five Viscera in Relation their part in Perfecting Life, "The Heart is in accord with the pulse. The complexion of a person shows when the heart is in a splendid condition. The heart rules over the kidneys. . . . . . . . The importance of assessing the functional state of the heart was realised even by the early Egyptian physicians in the 17th Century B.C. as described in the Ebers Papyrus:- "The begining of the physician, secret : knowledge of the heart's movements and knowledge of the heart. There are vessels from it to every limb. As to this, when any physician, any surgeon, or any exorcist applies the hands or his fingers to the head, to the back of the head, to the hands to the place of the stomach, to the arms or to the feet, then he examines the heart, because all his limbs possess its vessels, that is, the heart speaks out of the vessels of every limb".